2015
DOI: 10.1177/1941738115622138
|View full text |Cite
|
Sign up to set email alerts
|

Results After Anterior Cruciate Ligament Reconstruction in Patients Older Than 40 Years

Abstract: Context:Anterior cruciate ligament (ACL) reconstruction in older patients is a controversial topic among orthopaedic surgeons.Objective:To determine the outcomes, failure, and morbidity associated with ACL reconstruction in patients older than 40 years and to compare it with nonoperative treatment as well as results of ACL reconstruction in a younger patient population.Data Sources:A systematic review of the literature from 1970 to 2015 was conducted utilizing MEDLINE, CINAHL, and the Cochrane Central Register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 33 publications
(88 reference statements)
1
25
0
Order By: Relevance
“…Historically, ACL reconstruction has been recommended for the young, active population with symptomatic ACL tears. Other authors 19,25 have advocated for ACL reconstruction to prevent meniscal and cartilage injuries in chronically unstable knees, both of which are associated with poor function and rapid progression of knee degenerative changes. The treatment of ACL tears in the elderly population is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, ACL reconstruction has been recommended for the young, active population with symptomatic ACL tears. Other authors 19,25 have advocated for ACL reconstruction to prevent meniscal and cartilage injuries in chronically unstable knees, both of which are associated with poor function and rapid progression of knee degenerative changes. The treatment of ACL tears in the elderly population is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…19 Moreover, ACL reconstruction has been demonstrated to result in greater improvements in quality-adjusted life-years at a lower cost compared with nonoperative intervention. 20 With the advent of an anatomic surgical technique, the availability of enhanced instrumentation, the use of an improved and more aggressive rehabilitation protocol, and a better understanding of the immediate and long-term consequences of untreated knee instability, surgical indications for ACL insufficiency have been extended to active patients of all ages.…”
mentioning
confidence: 99%
“… 10 , 18 Nishio et al 37 reported that equivalent clinical outcomes (Lysholm and IKDC scores) were observed between 2 age groups (patients ≥40 and <40 years of age) after DB-ACLR. Mall et al 31 reported a systematic review of the results of single-bundle ACLR in patients aged >40 years. They reported that the outcomes were similar to those in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most common knee surgery is anterior cruciate ligament (ACL) reconstruction. It produces early return to sport and good clinical outcomes [1], [2], [3], [4], [5], [6], [7]. The outcomes are affected by various factors, such as type of grafts, graft fixation methods, tunnel orientations, graft diameters, and rehabilitation program.…”
Section: Introductionmentioning
confidence: 99%